2015
DOI: 10.3201/eid2111.150778
|View full text |Cite
|
Sign up to set email alerts
|

No Geographic Correlation between Lyme Disease and Death Due to 4 Neurodegenerative Disorders, United States, 2001–2010

Abstract: Death rates for these disorders were not associated with incidence of confirmed Lyme disease cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 21 publications
2
6
0
Order By: Relevance
“…[3], [11], [12], hampered by selection bias [11] or with no adequate comparison cohort [11], [14]. Despite the long-term follow-up in our large cohort of LNB patients, we were not able to demonstrate any increased risk of dementia, Alzheimer's disease, Parkinson's disease and motor neuron disease, which is consistent with a geoepidemiology study from the US in which there was no association between the geographical distribution of Lyme disease and the geographical distribution of these neurological disorders [16]. In fact, LNB patients might be subject to detection bias inferred by the diagnostic work-up during and after diagnosis thus increasing the likelihood of diagnosing subclinical dementia, Alzheimer's disease, Parkinson's disease and motor neuron disease [17].…”
Section: Discussion Of Our Own Results and Comparison With Other Studiessupporting
confidence: 49%
“…[3], [11], [12], hampered by selection bias [11] or with no adequate comparison cohort [11], [14]. Despite the long-term follow-up in our large cohort of LNB patients, we were not able to demonstrate any increased risk of dementia, Alzheimer's disease, Parkinson's disease and motor neuron disease, which is consistent with a geoepidemiology study from the US in which there was no association between the geographical distribution of Lyme disease and the geographical distribution of these neurological disorders [16]. In fact, LNB patients might be subject to detection bias inferred by the diagnostic work-up during and after diagnosis thus increasing the likelihood of diagnosing subclinical dementia, Alzheimer's disease, Parkinson's disease and motor neuron disease [17].…”
Section: Discussion Of Our Own Results and Comparison With Other Studiessupporting
confidence: 49%
“…In fact, the prevalence rate of 4.1% in patients with ALS is similar to the seroprevalence in the normal population of The Netherlands [15]. This is the first casecontrol study to examine the hypothesized link between B. burgdorferi antibodies and ALS, but previous studies with different designs found, as in the present study, a lack of association between Lyme-related antibodies and ALS [1][2][3]16]. In this study we took advantage of the availability of a large set of healthy controls from an ongoing population-based study aimed at identifying environmental, lifestyle and genetic risk factors for ALS.…”
Section: Discussionsupporting
confidence: 74%
“…Another study found no geographical correlation between LD and death due to Alzheimer’s disease [ 147 ]. A similar debate occurred over 100 years ago regarding the cause of general paresis which was proven when Noguchi and Moore demonstrated Treponema pallidum in brain autopsies of general paresis patients [ 148 ]. The many similarities between syphilis and LB are noted, brain autopsy studies with direct detection methods are the best approach to research this issue is with autopsy studies with direct detection methods which have demonstrated an association between LB and dementia [ 22 , 149 , 150 , 151 ].…”
Section: Resultsmentioning
confidence: 94%